2007
DOI: 10.1007/s10464-007-9087-2
|View full text |Cite
|
Sign up to set email alerts
|

African American adolescent mothers and grandmothers: A multigenerational approach to parenting

Abstract: This study is an adaptation and extension of Apfel and Seitz's (Family Relations, 40(4), 421-429, 1991) models of adolescent parenting and adolescent-grandmother relationships to a sample of 148 African American, first-time adolescent mothers and their 6-month-old infants. The Parental Supplemental model, in which adolescent mothers and grandmothers shared caregiving, described 63% of Apfel and Seitz's (1991) sample and 66% of the current sample. Shared caregiving was not associated with conflict in the adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…8 Indeed, perhaps the concept of 'learning together' should be extended to include all participants in the post-natal experience (midwives, new mothers, their significant others and the wider community) to ensure consistent, evidence-based strategies are implemented by all to foster breastfeeding success. Such a ''multilayered approach'' to breastfeeding support is in line with recommendations by Lavender et al 28 Because having a supportive relationship with their own mothers is positively associated with new mothers feeling more competent as parents 31 and lowered grandmother selfesteem has been associated with new mother depression 26 ; it is essential to understand how grandmothers cope with role strain and conflict and what factors are enhancing for their self-esteem and the grandmother/new mother relationship. Further research into the complexity of the grandmother/ new mother relationship that includes the new mother's perspective is needed to allow greater understanding of the way in which new mothers give meaning to all the verbal and non-verbal messages they receive and how they validate and use the information and advice that is available explicitly and implicitly to them.…”
Section: Conclusion and Implications For Practicementioning
confidence: 66%
“…8 Indeed, perhaps the concept of 'learning together' should be extended to include all participants in the post-natal experience (midwives, new mothers, their significant others and the wider community) to ensure consistent, evidence-based strategies are implemented by all to foster breastfeeding success. Such a ''multilayered approach'' to breastfeeding support is in line with recommendations by Lavender et al 28 Because having a supportive relationship with their own mothers is positively associated with new mothers feeling more competent as parents 31 and lowered grandmother selfesteem has been associated with new mother depression 26 ; it is essential to understand how grandmothers cope with role strain and conflict and what factors are enhancing for their self-esteem and the grandmother/new mother relationship. Further research into the complexity of the grandmother/ new mother relationship that includes the new mother's perspective is needed to allow greater understanding of the way in which new mothers give meaning to all the verbal and non-verbal messages they receive and how they validate and use the information and advice that is available explicitly and implicitly to them.…”
Section: Conclusion and Implications For Practicementioning
confidence: 66%
“…Health workers found it difficult to work with these families, because they perceived the need of taking care of both the teens and their mothers, and they found that this latter duty was not easy. The literature has already indicated that a supportive grandmother was a protective factor for the teen's well-being and could enhance also outcomes for the teen mother's child (Dallas, 2004;Oberlander, Black, & Starr, 2007). However, a high level of grandmother involvement appeared to be related to negative consequences for the teen mother's child, because it may inadvertently encourage her to be less involved with her child (Cooley & Unger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…They were disproportionately female, younger, and less educated than non-caregivers (Oberlander, Black, & Starr, 2007) and more likely to be living in poverty and receiving public assistance. Grandmother caregivers had significantly higher rates of functional limitations and poverty than either grandfather caregivers or other African American women aged 45C (Minkler & Fuller-Thomson, 2005).…”
Section: African American Grand-parenting Trends Challenges and Benmentioning
confidence: 99%